The Analysis Study of Relationship of Psoriasis and Hypertension: A Comprehensive Systematic Review - Melinda Angelin; Muhammad Faiz Haidar Rafi (The International Journal of Medical Science and Health Research, 2025)
Background: Psoriasis patients have a higher prevalence of hypertension, a significant risk factor for cardiovascular disease. The association between psoriasis and hypertension is complex, with psoriasis often presenting with additional risk factors. Treatment approaches are complex, and understanding the bidirectional relationship between psoriasis and hypertension is crucial for optimizing treatment strategies and improving patient care. Methods: This systematic review adhered to PRISMA 2020 guidelines, focusing exclusively on full-text articles published in English between 2014 and 2024. Editorials and review articles without a DOI were excluded to ensure the utilization of high-quality sources. A literature review was conducted utilizing reputable databases including ScienceDirect, PubMed, and SagePub to identify relevant studies. Result: The initial database search yielded over 1,000 relevant publications on the topic. Following a rigorous three-stage screening process, eight studies met the predefined inclusion criteria and were selected for in-depth analysis. Each study underwent a comprehensive critical evaluation, enabling a thorough examination of the relationship between psoriasis and hypertension. This systematic approach ensured that the analysis was grounded in high-quality evidence, closely aligned with the study's objectives, and capable of providing meaningful insights into this complex association. Conclusion: Psoriasis and hypertension are linked due to various factors, including confounding variables, shared inflammatory pathways, and treatment-related factors. Further research is needed to understand causal mechanisms and the impact of disease severity on hypertension risk. Understanding these factors will help healthcare providers develop personalized treatment approaches and improve patient outcomes for those affected by both conditions.